Evaluating the relationship between explicit and implicit drinking identity centrality and hazardous drinking. (December 2016) - Lindgren, Kristen P.; Ramirez, Jason J.; Namaky, Nauder; Olin, Cecilia C.; Teachman, Bethany A.
Abstract: Introduction: Drinking identity strength (how strongly one views oneself as a drinker) is a promising risk factor for hazardous drinking. A critical next step is to investigate whether the centrality of drinking identity (i.e., the relative importance of drinking vs. other identity domains, like well-being, relationships, education) also plays a role. Thus, we developed explicit and implicit measures of drinking identity centrality and evaluated them as predictors of hazardous drinking after controlling for explicit drinking identity strength. Methods: Two studies were conducted ( N s = 360 and 450, respectively). Participants, who self-identified as full-time students, completed measures of explicit identity strength, explicit and implicit centrality, and the Alcohol Use Disorders Identification Test (AUDIT). Study 1a evaluated two variants of the implicit measure (short- vs. long-format of the Multi-category Implicit Association Test); Study 1b only included the long form and also assessed alcohol consumption. Results: In Study 1a, implicit and explicit centrality measures were positively and significantly associated with AUDIT scores after controlling for explicit drinking identity strength. There were no significant differences in the implicit measure variants, but the long format had slightly higher internal consistency. In Study 1b, results replicated for explicit, but not implicit, centrality. Conclusions: These studies provide preliminary evidence that drinking identity centrality may be an important factor for predicting hazardous drinking. Future research should improve its measurement and evaluate implicit and explicit centrality in experimental and longitudinal studies. Highlights: We developed implicit and explicit measures of drinking identity centrality. They were evaluated as predictors of drinking in two, closely-related, studies. They were associated with drinking above and beyond drinking identity strength. The construct should be further evaluated and incorporated into theory. Measurement of drinking identity centrality should also be improved.